2020
DOI: 10.3892/etm.2020.9012
|View full text |Cite
|
Sign up to set email alerts
|

A decreasing trend in toxoplasma gondii seroprevalence among pregnant women in Romania�‑�results of a large scale study

Abstract: Toxoplasmosis is a zoonotic infection caused by the obligate intracellular apicomplexan parasite Toxoplasma gondii (T. gondii). T. gondii infection is a cause of congenital infection worldwide. Primary infection or the reactivation of latent infection during pregnancy may lead to fetal infection and to congenital toxoplasmosis syndrome. Seropositive pregnant women are generally protected from maternal-fetal transmission of T. gondii , although exceptions exist. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
4
16
1
Order By: Relevance
“…According to some results, T. gondii seroprevalence in pregnant women has decreased from 43.79 to 38.81% in the last 10 years in the Western Region of Romania. Our study, unlike other recent studies carried out in Romania, did not show statistically significant differences related to the age of the pregnant women infected with T. gondii ,while the prevalence of infections was higher in urban areas ( 36 , 37 ). Consistent with the two studies mentioned above, several authors claim that there is a decreasing trend in T. gondii infection among pregnant women ( 38 ).…”
Section: Discussioncontrasting
confidence: 99%
“…According to some results, T. gondii seroprevalence in pregnant women has decreased from 43.79 to 38.81% in the last 10 years in the Western Region of Romania. Our study, unlike other recent studies carried out in Romania, did not show statistically significant differences related to the age of the pregnant women infected with T. gondii ,while the prevalence of infections was higher in urban areas ( 36 , 37 ). Consistent with the two studies mentioned above, several authors claim that there is a decreasing trend in T. gondii infection among pregnant women ( 38 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This study is part of a larger project that demonstrated a decrease in the seroprevalence of Toxoplasma gondii , CMV and rubella virus, among women of reproductive age and pregnant women in western Romania over a decade from 2008 to 2018 [ 11 , 12 , 13 ]. Thus, our previous research showed a decrease in seroprevalence among women of reproductive age, between 2008–2010 and 2015–2018, from 43.8% to 38.8% [ 11 ], in the case of Toxoplasma gondii . Among the general population, the seroprevalence of Toxoplasma gondii is estimated at 25–30%, while among women of reproductive age, it varies between regions being 9.1% in the USA, 19% in Italy and 44% in France.…”
Section: Discussionmentioning
confidence: 99%
“…Among the risk factors associated with T. gondii seropositivity, the following are mentioned: the place of residence from the rural environment, the lower socioeconomic level, as well as the more frequent contact with the infected animals and soil. [ 11 ]. In the western region of Romania, our previous research showed also a decrease in CMV seroprevalence among women of reproductive age, from 94% to 91.8% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest study on the seroprevalence of TORCH infections among women of reproductive age in Romania [ 11 , 12 ]. The presented results show that the rubella seronegative rate among women of reproductive age in the western region of Romania increased between 2008–2010 and 2015–2018 from 5.9% to 8.6%, above the European average of 7.6% [ 7 ].…”
Section: Discussionmentioning
confidence: 99%